Metagenomic study for the identification of viruses infecting soybean in Pakistan - Rahman, Saleem Ur; Domier, Leslie L.; Raza, Ghulam; Ahmed, Nasim; McCoppin, Nancy K.; Amin, Imran; Mansoor, Shahid (Australasian plant pathology, 2023)
In 2018, symptoms of multiple viruses were observed in a soybean field at Faisalabad, Pakistan. Symptomatic and asymptomatic leaf samples were collected, RNA was extracted, and cDNA was synthesized and characterized using high throughput RNA sequencing (RNAseq). The RNAseq results showed the presence of three strains of cowpea mild mottle virus, an RNA virus in the Carlavirus genus in the family Betaflexiviridae . Eight contigs of a putative member of the genus Torradovirus in the family Secoviridae were also observed, which was named soybean torradovirus-1. Multiple DNA viruses of the genus Begomovirus were also identified. These included mungbean yellow mosaic India virus, mungbean yellow mosaic virus and pedilanthus leaf curl virus. Among the RNA and DNA viruses, cowpea mild mottle virus and mungbean yellow mosaic virus were the most abundant.